Bile-Salt-Hydrolases from the Probiotic Strain Lactobacillus johnsonii La1 Mediate Anti-giardial Activity in Vitro and in Vivo - Allain, Thibault; Chaouch, Soraya; Thomas, Myriam; Vallée, Isabelle; Buret, André G.; Langella, Philippe; Grellier, Philippe; Polack, Bruno; Bermúdez-Humarán, Luis G.; Florent, Isabelle (Frontiers in Microbiology, 2018)
Giardia duodenalis (syn. G. lamblia, G intestinalis) is the protozoan parasite responsible for giardiasis, the most common and widely spread intestinal parasitic disease worldwide, affecting both human and animals. After cysts ingestion (through either contaminated food or water), Giardia excysts in the upper intestinal tract to release replicating trophozoites that are responsible for the production of symptoms. In the gut, Giardia cohabits with the host’s microbiota and several studies have revealed the importance of this gut ecosystem and/or some probiotic bacteria in providing protection against G. duodenalis infection through mechanisms that remain incompletely understood. Recent findings suggest that Bile-Salt-Hydrolase (BSH)-like activities from the probiotic strain of Lactobacillus johnsonii La1 may contribute to the anti-giardial activity displayed by this strain. Here, we cloned and expressed each of the three bsh genes present in the L. johnsonii La1 genome to study their enzymatic and biological properties. Whereas BSH47 and BSH56 were expressed as recombinant active enzymes, no significant enzymatic activity was detected with BSH12. In vitro assays allowed determining the substrate specificities of both BSH47 and BSH56, which were different. Modeling of these BSHs indicated a strong conservation of their 3-D structures despite low conservation of their primary structures. Both recombinant enzymes were able to mediate anti-giardial biological activity against Giardia trophozoites in vitro. Moreover, BSH47 exerted significant anti-giardial effects, when tested in a murine model of giardiasis. These results shed new light on the mechanism whereby active BSH derived from the probiotic strain Lactobacillus johnsonii La1 may yield anti-giardial effects in vitro and in vivo. These findings pave the way towards novel approaches for the treatment of this widely spread but neglected infectious disease, both in human and in veterinary medicine.